Key differences in combat tactics, action triggers and self-commands in taekwondo and boxing - Malkov, O. B.; Romashov, A. A. (Theory and Practice of Physical Culture, 2018)
Success of tactical actions in combat sports largely depends on the individual offence timing qualities and skills. The timing skills may be classified as follows: the trigger moment detection and initiation components; willpower release form i.e. self-command or counteraction. The article analyzes the mental control mechanisms in charge of the action triggers and self-commands depending on the mental processes associated with the actions. The relevant psychomotor responses may be classified versus the athletes` fitness rates, with the key role played by the anticipation qualities and skills and their harmony with the other mental qualities for success of the intended and spontaneous actions on self-commands upon the opponent`s action precursor is perceived in the bout. Good understanding of own response control logics in the bouts enables an athlete to mobilize the relevant self-commanding, trigger signal anticipation and response mechanisms as dictated by the fight situation. The timing skill analysis and logics may be beneficial for the training and educational process design and management in the modern martial arts.